A multilayer waterborne polyurethane-based composite absorbing material and a preparation method thereof
Through the design of multi-layer water-based polyurethane-based composite absorbing material, the composite structure of MXene and iron tetraoxide and water-based polyurethane is used to solve the problem of poor absorption effect of a single microwave loss material under low matching thickness, and the effect of efficient absorption of electromagnetic waves at low thickness is achieved.
Patent Information
- Application Number
- CN202411785522.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-06
AI Technical Summary
It is difficult for existing single microwave loss materials to achieve excellent electromagnetic wave absorption effect at low matching thicknesses, and traditional designs are difficult to meet the requirements of light weight, thin thickness, strong absorption characteristics and microwave absorption bandwidth.
The design of multi-layer water-based polyurethane-based composite absorbing materials is adopted, and aqueous polyurethane, MXene and iron tetraoxide are prepared through prepolymer method, etching method and hydrothermal method to form MXene/ferrous tetraoxide/water-based polyurethane composite absorbing materials. The sandwich structure of the reflective layer, absorption layer and matching layer is used to achieve the "absorption-reflection-reabsorbing" mechanism.
The absorption rate of electromagnetic waves is significantly improved at a lower matching thickness, and the material has excellent absorbing performance and good flexibility, which is suitable for a wide range of application scenarios.
Smart Images

Figure CN119261340B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer-based wave-absorbing materials and relates to a multi-layer waterborne polyurethane-based composite wave-absorbing material and a preparation method thereof. Background Art
[0002] With the advancement of technology and the development of society, people's daily lives are surrounded by electronic devices such as mobile phones and laptops, which can facilitate communication between each other. However, the electromagnetic pollution caused by electronic devices is inevitable and has become more and more serious over time. It has become the fourth largest public hazard in the field of environmental protection. Therefore, researchers pay more attention to microwave absorbing materials to reduce electromagnetic pollution.
[0003] Microwave absorbing materials have the characteristics of light weight, wide bandwidth, thin coating, and strong reflection loss. Traditionally, the research on microwave absorbing materials has focused on dielectric or magnetic loss materials, such as metal oxides and carbon-based materials. However, it is difficult to meet the requirements of microwave absorbing materials using a single microwave loss material. Due to impedance mismatch and a single microwave loss mechanism, a single microwave loss material cannot meet the requirements of light weight, thin thickness, strong absorption characteristics, and microwave absorption bandwidth.
[0004] The electromagnetic synergy strategy has been proven to be an effective method to significantly reduce the matching thickness required for reflection loss. However, for current single-phase absorbing materials, it is still a challenge to improve the electromagnetic wave absorption effect at low matching thickness. Multilayer structure design is more likely to obtain high absorption capacity and low matching thickness, and the use of polymer matrix can improve the application scenarios of the material. Therefore, it is of great significance to study a multilayer waterborne polyurethane-based composite absorbing material and its preparation method.
[0005] Based on this, the present invention aims to provide a multi-layer waterborne polyurethane-based composite absorbing material that meets the requirement of improving the electromagnetic wave absorption effect under the condition of low matching thickness. Summary of the invention
[0006] In view of the above technical problems, the present invention aims to provide a multilayer waterborne polyurethane-based composite absorbing material and a preparation method thereof. The method uses a prepolymer method, an etching method and a hydrothermal method to prepare waterborne polyurethane, MXene and ferroferric oxide respectively, and then prepares a MXene / ferroferric oxide / waterborne polyurethane composite absorbing material with a multilayer structure by a curing method; the bottom layer of the composite absorbing material is a reflective layer containing MXene@waterborne polyurethane, the middle layer is an absorbing layer of ferroferric oxide@waterborne polyurethane, and the waterborne polyurethane matching layer is between the two functional layers and on the top layer of the composite material. This sandwich structure enables the composite absorbing material to effectively absorb incident electromagnetic waves, and improves the absorption rate of electromagnetic waves through the "absorption-reflection-reabsorption" mechanism, so that the composite absorbing material has excellent absorbing performance and good flexibility at a lower matching thickness.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A multi-layer waterborne polyurethane-based composite absorbing material comprises, from bottom to top, a reflection layer, a matching layer, an absorption layer, and a matching layer; the reflection layer is MXene@waterborne polyurethane, the matching layers are all waterborne polyurethane, and the absorption layer is ferroferric oxide@waterborne polyurethane.
[0009] The present invention also provides a method for preparing a multi-layer waterborne polyurethane-based composite absorbing material, which is carried out in the following steps in sequence:
[0010] (1) Preparation of waterborne polyurethane
[0011] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were placed in a three-necked flask and prepolymerized at 80-100°C for 1-3 h, then 10 μL of dibutyltin dilaurate was added and reacted for 2-4 h, then 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone were added and reacted for 2-4 h, finally the system was cooled to 25-40°C and 8 mmol of triethylamine was added and reacted for 20-40 min, and then 50 mL of deionized water was added and reacted for 10-30 min to obtain waterborne polyurethane;
[0012] (2) Preparation of MXene
[0013] Put hydrochloric acid in a polytetrafluoroethylene beaker and slowly add lithium fluoride to stir the reaction at room temperature and 500-800 rpm for 3-8 min, then slowly add titanium carbide and transfer the beaker to a 50-70°C oil bath, stir the reaction at 600-800 rpm for 8-14 h, then centrifuge the solution for the first time, wash with 0.5-2 mol / L hydrochloric acid and ultrapure water respectively until the solution is neutral, finally add 20 mL of ultrapure water to the centrifuge tube, shake for 20-40 min and then centrifuge for the second time to obtain MXene;
[0014] (3) Preparation of Fe3O4
[0015] Dissolve 1.6 g of anhydrous ferric chloride and 5.9 g of sodium citrate dihydrate in 160 mL of deionized water in sequence, then add 2 g of thiourea to the above solution, and then gradually add 2 g of sodium polyacrylate, stir at room temperature at a speed of 300-500 rpm for 8-14 h, then add the solution to a polytetrafluoroethylene-lined stainless steel reactor, and react at 160-220°C for 8-14 h to generate ferrosoferric oxide;
[0016] (4) Preparation of multi-layer waterborne polyurethane-based composite absorbing materials
[0017] MXene and ferroferric oxide are mixed with waterborne polyurethane to obtain MXene@waterborne polyurethane and ferroferric oxide@waterborne polyurethane respectively;
[0018] 1200 mg MXene@waterborne polyurethane was added into a polytetrafluoroethylene mold and the system was opened and allowed to stand. Then, 400 mg waterborne polyurethane, 1100-1600 mg ferrosirroxide@waterborne polyurethane, and 400 mg waterborne polyurethane were added into the mold in sequence, and the system was opened and allowed to stand in sequence to obtain a multilayer waterborne polyurethane-based composite absorbing material.
[0019] As a limitation of the preparation method of the present invention, in step (2), the molar ratio of hydrochloric acid, lithium fluoride and titanium aluminum carbide is 22.5:4.75:1.
[0020] As another limitation of the preparation method of the present invention, in step (2), the speed of the first centrifugation is 4000-7000 rpm, and the time is 5-20 min; the speed of the second centrifugation is 2000-5000 rpm, and the time is 10-30 min.
[0021] As a third limitation of the preparation method of the present invention, in step (4), the mass ratio of MXene to waterborne polyurethane is 200:1000, and the mass ratio of ferrosoferric oxide to waterborne polyurethane is 100-600:1000.
[0022] As a fourth limitation of the preparation method of the present invention, in step (4), the standing time is 6-12 h.
[0023] The present invention prepares a MXene / ferroferric oxide / waterborne polyurethane composite absorbing material with a multilayer structure by a curing method. First, MXene is dispersed in waterborne polyurethane. Since the diketone brought by the chain extender curcumin in the waterborne polyurethane and its enol tautomer structure are easy to have strong hydrogen bonds and π electron interactions with the surface terminal groups of MXene and ferroferric oxide particles, it is beneficial for MXene and ferroferric oxide particles to be evenly and stably distributed in the waterborne polyurethane and generate strong interaction forces. A matching layer is prepared between the reflective layer and the absorbing layer by using a large number of hydrogen bonds formed by the abundant N and O groups of the waterborne polyurethane itself, so that the matching layer generates hydrogen bonds with the waterborne polyurethane in the two functional layers and entanglement between molecular chains. Finally, a matching layer is covered on the absorbing layer by the same principle. At the same time, the matching layer plays a protective role, so that the functional filler is not easily corroded or oxidized by acid. Due to a large number of strong hydrogen bonds, π electron interactions and molecular chain entanglement, the multilayered MXene / ferroferric oxide / waterborne polyurethane composite absorber has a very large elongation at break and good flexibility. At the same time, a large number of hydrogen bonds can make the polyurethane matrix have certain self-healing properties and extend its life.
[0024] The multilayer structure of MXene / ferroferric oxide / waterborne polyurethane composite absorber enables it to have the synergistic effect of different loss mechanisms, rich heterogeneous interfaces and the comprehensive effect of multiple reflection and scattering, so that the absorber has low matching thickness, excellent absorbing performance and rich application scenarios. When the incident electromagnetic wave contacts the surface layer of the composite material, the matching layer effectively adjusts the impedance matching between the surface layer and the air, which allows more electromagnetic waves to enter the composite material. The electromagnetic wave interacts with the ferroferric oxide particles in the absorption layer, generating ferromagnetic resonance and eddy current loss to reduce the energy of the incident electromagnetic wave. Due to the different conductivity between the reflection layer and the intermediate matching layer, impedance mismatch occurs when the incident electromagnetic wave contacts the reflection layer. Therefore, some electromagnetic waves are reflected and returned to the absorption layer and interact with the magnetic particles again. The remaining electromagnetic waves enter the reflection layer and generate polarization losses under the dipole polarization of the MXene surface functional groups. In addition, MXene and ferroferric oxide particles have abundant interfaces in waterborne polyurethane and form local conductive pathways, resulting in severe interface polarization loss and conductive loss, which further weaken the energy of electromagnetic waves under the action of magnetic dipoles and electric dipoles. In the multi-layered waterborne polyurethane-based composite absorber, electromagnetic waves undergo the process of "absorption-reflection-reabsorption", in which the electromagnetic waves entering the absorption layer are first absorbed, and the remaining electromagnetic waves are reflected by the reflection layer and reabsorbed by the absorption layer. This absorption process effectively reduces the reflection of the incident electromagnetic waves, thereby reducing their secondary pollution to the environment. The MXene, which is easily oxidized in the dielectric loss layer, is also protected by the waterborne polyurethane, ensuring the performance stability of the composite material during use.
[0025] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0026] The above technical solution has the following advantages or beneficial effects:
[0027] 1. The present invention utilizes a prepolymer method, an etching method, and a hydrothermal method to prepare waterborne polyurethane, MXene, and ferroferric oxide, respectively, and prepares a multilayer waterborne polyurethane-based composite absorbing material through mixing and static laying of an open system. This method has a simple preparation process, and the prepared multilayer waterborne polyurethane-based composite absorbing material has excellent performance and a wide range of applications.
[0028] 2. The present invention places MXene@waterborne polyurethane in the bottom layer as a reflective layer, ferroferric oxide@waterborne polyurethane as an absorption layer, and two layers of waterborne polyurethane as matching layers to prepare a multilayer absorbing material. The multilayer waterborne polyurethane-based composite absorbing material has the synergistic effect of different loss mechanisms inside, rich heterogeneous interfaces and the comprehensive effect of multiple reflection and scattering, which makes the multilayer waterborne polyurethane-based composite absorbing material have excellent absorbing performance at a lower matching thickness. At the same time, good flexibility gives the material a wider range of application scenarios.
[0029] The invention is suitable for preparing a multi-layer polyurethane-based composite wave-absorbing material.
[0030] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of microwave loss of the multi-layer waterborne polyurethane-based composite absorbing material of the present invention;
[0032] Figure 2 This is the XRD pattern of the multi-layer waterborne polyurethane-based composite absorbing material prepared in Example 2 of the present invention;
[0033] Figure 3 This is a SEM image of the multi-layer waterborne polyurethane-based composite absorbing material prepared in Example 2 of the present invention;
[0034] Figure 4 This is a graph showing the microwave loss capacity of the multi-layer waterborne polyurethane-based composite absorbing material with different thicknesses prepared in Example 1 of the present invention as a function of frequency;
[0035] Figure 5 This is a graph showing the microwave loss capacity of the multi-layer waterborne polyurethane-based composite absorbing material with different thicknesses prepared in Example 2 of the present invention as a function of frequency;
[0036] Figure 6 This is a graph showing the microwave loss capacity of the multi-layer waterborne polyurethane-based composite absorbing material with different thicknesses prepared in Example 3 of the present invention as a function of frequency;
[0037] Figure 7 This is a graph showing the microwave loss capacity of the waterborne polyurethane absorbing material of different thicknesses prepared in Comparative Example 1 of the present invention as a function of frequency;
[0038] Figure 8 This is a graph showing the microwave loss capacity of the MXene@waterborne polyurethane absorbing material of different thicknesses prepared in Comparative Example 2 of the present invention as a function of frequency;
[0039] Fig. 9This is a graph showing the microwave loss capacity of the ferroferric oxide@waterborne polyurethane absorbing material of different thicknesses prepared in Comparative Example 3 of the present invention as a function of frequency;
[0040] Fig.10 This is a graph showing the stress-strain variation of the multi-layer waterborne polyurethane-based composite absorbing material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0041] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0042] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified. Example 1
[0043] This embodiment prepares a multi-layer waterborne polyurethane-based composite absorbing material, and the preparation process and steps are as follows:
[0044] (1) Preparation of waterborne polyurethane
[0045] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were weighed and put into a three-necked flask for prepolymerization at 80°C for 1 hour, and then 10 μL of dibutyltin dilaurate was added to continue the reaction for 2 hours, followed by the addition of 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone to continue the reaction for 3 hours. After the reaction was completed, the system was cooled to 35°C and 8 mmol of triethylamine was added to react for 30 minutes, and finally 50 mL of deionized water was added and stirred for 20 minutes to obtain waterborne polyurethane.
[0046] (2) Preparation of MXene
[0047] 22.5 mol of hydrochloric acid was measured and placed in a polytetrafluoroethylene beaker, and 4.75 mol of lithium fluoride was added to react at room temperature and 720 rpm magnetic stirring for 3 min, then 1 mol of titanium aluminum carbide was slowly added and the beaker was transferred to a 60°C oil bath. After continuous reaction at 720 rpm magnetic stirring for 12 h, the solution was centrifuged at 5000 rpm for 15 min, and then washed with 1 mol / L hydrochloric acid and ultrapure water respectively until the solution was neutral. Finally, 20 mL of ultrapure water was added to the centrifuge tube, shaken for 20 min, and centrifuged at 3000 rpm for 20 min to obtain a MXene solution.
[0048] (3) Preparation of Fe3O4
[0049] 1.6 g of anhydrous ferric chloride and 5.9 g of sodium citrate dihydrate were weighed and dissolved in 160 mL of deionized water, and then 2 g of thiourea was added to the above solution, and then 2 g of sodium polyacrylate was gradually added. The mixture was stirred at 300 rmp for 8 h at room temperature, and then the solution was added to a polytetrafluoroethylene-lined stainless steel reactor and reacted at 200 °C for 12 h to generate ferrosoferric oxide nanoparticles.
[0050] (4) Preparation of multi-layer waterborne polyurethane-based composite absorbing materials
[0051] Weigh 200 mg of MXene and 1000 mg of waterborne polyurethane and mix them evenly to prepare a MXene@waterborne polyurethane mixed solution, and then weigh 100 mg of ferroferric oxide and 1000 mg of waterborne polyurethane and mix them evenly to prepare a ferroferric oxide@waterborne polyurethane mixed solution;
[0052] 1200 mg MXene@waterborne polyurethane was added into the open system in the polytetrafluoroethylene mold and allowed to stand for 6 h. Then 400 mg waterborne polyurethane was added into the open system and allowed to stand for 6 h. Then 1100 mg ferrosoferric oxide@waterborne polyurethane was added into the open system and allowed to stand for 6 h. Finally, 400 mg waterborne polyurethane was added into the open system and allowed to stand for 6 h to obtain a multilayer waterborne polyurethane-based composite absorbing material.
[0053] The multilayer waterborne polyurethane-based composite absorbing material prepared in this embodiment can effectively absorb incident electromagnetic waves and has excellent absorbing performance at a relatively low matching thickness. Example 2
[0054] This embodiment prepares a multi-layer waterborne polyurethane-based composite absorbing material, and the preparation process and steps are as follows:
[0055] (1) Preparation of waterborne polyurethane
[0056] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were weighed and put into a three-necked flask for prepolymerization at 100°C for 3 h, and then 10 μL of dibutyltin dilaurate was added to continue the reaction for 4 h, followed by the addition of 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone for a further 2 h. After the reaction was completed, the system was cooled to 25°C and 8 mmol of triethylamine was added to react for 20 min, and finally 50 mL of deionized water was added and stirred for 10 min to obtain waterborne polyurethane.
[0057] (2) Preparation of MXene
[0058] 22.5 mol of hydrochloric acid was measured and placed in a polytetrafluoroethylene beaker, and 4.75 mol of lithium fluoride was added to react at room temperature and 500 rpm magnetic stirring for 5 min, then 1 mol of titanium aluminum carbide was slowly added and the beaker was transferred to a 50°C oil bath. After continuous reaction at 600 rpm magnetic stirring for 8 h, the solution was centrifuged at 4000 rpm for 5 min, and then washed with 0.5 mol / L hydrochloric acid and ultrapure water respectively until the solution was neutral. Finally, 20 mL of ultrapure water was added to the centrifuge tube, shaken for 30 min, and centrifuged at 2000 rpm for 10 min to obtain a MXene solution.
[0059] (3) Preparation of Fe3O4
[0060] 1.6 g of anhydrous ferric chloride and 5.9 g of sodium citrate dihydrate were weighed and dissolved in 160 mL of deionized water, and then 2 g of thiourea was added to the above solution, and then 2 g of sodium polyacrylate was gradually added. The mixture was stirred at 450 rpm for 10 h at room temperature, and then the solution was added to a polytetrafluoroethylene-lined stainless steel reactor and reacted at 160 ° C for 8 h to generate ferrosoferric oxide nanoparticles.
[0061] (4) Preparation of multi-layer waterborne polyurethane-based composite absorbing materials
[0062] Weigh 200 mg of MXene and 1000 mg of waterborne polyurethane and mix them evenly to prepare a MXene@waterborne polyurethane mixed solution; weigh 400 mg of ferroferric oxide and 1000 mg of waterborne polyurethane and mix them evenly to prepare a ferroferric oxide@waterborne polyurethane mixed solution;
[0063] 1200 mg MXene@waterborne polyurethane was added into the open system in the polytetrafluoroethylene mold and allowed to stand for 10 h. Then 400 mg waterborne polyurethane was added into the open system and allowed to stand for 10 h. Then 1400 mg ferrosoferric oxide@waterborne polyurethane was added into the open system and allowed to stand for 10 h. Finally, 400 mg waterborne polyurethane was added into the open system and allowed to stand for 10 h to obtain a multilayer waterborne polyurethane-based composite absorbing material.
[0064] The multilayer waterborne polyurethane-based composite absorbing material prepared in this embodiment can effectively absorb incident electromagnetic waves and has excellent absorbing performance at a relatively low matching thickness. Example 3
[0065] This embodiment prepares a multi-layer waterborne polyurethane-based composite absorbing material, and the preparation process and steps are as follows:
[0066] (1) Preparation of waterborne polyurethane
[0067] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were weighed and put into a three-necked flask for prepolymerization at 90°C for 2 h, and then 10 μL of dibutyltin dilaurate was added to continue the reaction for 3 h, followed by the addition of 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone to continue the reaction for 4 h. After the reaction was completed, the system was cooled to 40°C and 8 mmol of triethylamine was added to react for 40 min, and finally 50 mL of deionized water was added and stirred for 30 min to obtain waterborne polyurethane.
[0068] (2) Preparation of MXene
[0069] 22.5 mol of hydrochloric acid was measured and placed in a polytetrafluoroethylene beaker, and 4.75 mol of lithium fluoride was added to react at room temperature and 800 rpm magnetic stirring for 8 min, then 1 mol of titanium aluminum carbide was slowly added and the beaker was transferred to a 70°C oil bath. After continuous reaction at 800 rpm magnetic stirring for 14 h, the solution was centrifuged at 7000 rpm for 20 min, and then washed with 2 mol / L hydrochloric acid and ultrapure water respectively until the solution was neutral. Finally, 20 mL of ultrapure water was added to the centrifuge tube, shaken for 40 min, and centrifuged at 5000 rpm for 30 min to obtain a MXene solution.
[0070] (3) Preparation of Fe3O4
[0071] 1.6 g of anhydrous ferric chloride and 5.9 g of sodium citrate dihydrate were weighed and dissolved in 160 mL of deionized water, and then 2 g of thiourea was added to the above solution, and then 2 g of sodium polyacrylate was gradually added. The mixture was stirred at 500 rmp for 14 h at room temperature, and then the solution was added to a polytetrafluoroethylene-lined stainless steel reactor and reacted at 220 °C for 14 h to generate ferrosoferric oxide nanoparticles.
[0072] (4) Preparation of multi-layer waterborne polyurethane-based composite absorbing materials
[0073] Weigh 200 mg of MXene and 1000 mg of waterborne polyurethane and mix them evenly to prepare a MXene@waterborne polyurethane mixed solution; weigh 600 mg of ferroferric oxide and 1000 mg of waterborne polyurethane and mix them evenly to prepare a ferroferric oxide@waterborne polyurethane mixed solution;
[0074] 1200 mg MXene@waterborne polyurethane was added into the open system in the polytetrafluoroethylene mold and allowed to stand for 12 h. Then 400 mg waterborne polyurethane was added into the open system and allowed to stand for 12 h. Then 1600 mg ferrosoferric oxide@waterborne polyurethane was added into the open system and allowed to stand for 12 h. Finally, 400 mg waterborne polyurethane was added into the open system and allowed to stand for 12 h to obtain a multilayer waterborne polyurethane-based composite absorbing material.
[0075] The multilayer waterborne polyurethane-based composite absorbing material prepared in this embodiment can effectively absorb incident electromagnetic waves and has excellent absorbing performance at a relatively low matching thickness. Comparative Example
[0076] In order to explore the influence of different absorbing materials on the absorbing performance, the following comparative experiments were carried out. Different absorbing materials were prepared in the following comparative examples, as follows: Comparative Example 1
[0077] This comparative example prepares a single-layer pure waterborne polyurethane absorbing material, and the specific preparation process is as follows:
[0078] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were weighed and put into a three-necked flask for prepolymerization at 80°C for 1 hour, and then 10 μL of dibutyltin dilaurate was added to continue the reaction for 2 hours, followed by the addition of 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone to continue the reaction for 3 hours. After the reaction was completed, the system was cooled to 35°C and 8 mmol of triethylamine was added to react for 30 minutes, and finally 50 mL of deionized water was added and stirred for 20 minutes to obtain waterborne polyurethane.
[0079] 1200 mg of waterborne polyurethane was weighed and poured into a polytetrafluoroethylene mold and allowed to stand in an open system for 7 h to obtain a pure waterborne polyurethane absorbing material. Comparative Example 2
[0080] This comparative example prepares a single-layer MXene@waterborne polyurethane composite absorbing material, and the specific preparation process is as follows:
[0081] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were weighed and put into a three-necked flask for prepolymerization at 80°C for 1 hour, and then 10 μL of dibutyltin dilaurate was added to continue the reaction for 2 hours, followed by the addition of 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone to continue the reaction for 3 hours. After the reaction was completed, the system was cooled to 35°C and 8 mmol of triethylamine was added to react for 30 minutes, and finally 50 mL of deionized water was added and stirred for 20 minutes to obtain waterborne polyurethane.
[0082] 22.5 mol of hydrochloric acid was measured and placed in a polytetrafluoroethylene beaker, and 4.75 mol of lithium fluoride was added to react at room temperature and 720 rpm magnetic stirring for 5 min. Then 1 mol of titanium aluminum carbide was slowly added and the beaker was transferred to a 60°C oil bath. After continuous reaction at 720 rpm magnetic stirring for 12 h, the solution was centrifuged at 5000 rpm for 15 min, and then washed with 1 mol / L hydrochloric acid and ultrapure water respectively until the solution was neutral. Finally, 20 mL of ultrapure water was added to the centrifuge tube, shaken for 20 min, and centrifuged at 3000 rpm for 20 min to obtain MXene.
[0083] 200 mg MXene and 1000 mg waterborne polyurethane were weighed and evenly mixed to prepare a MXene@waterborne polyurethane mixed solution. The MXene@waterborne polyurethane mixed solution was poured into a polytetrafluoroethylene mold and allowed to stand in an open system for 7 hours to obtain a single-layer MXene@waterborne polyurethane composite absorbing material. Comparative Example 3
[0084] This comparative example prepares a single-layer ferroferric oxide@waterborne polyurethane composite absorbing material, and the specific preparation process is as follows:
[0085] 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were weighed and put into a three-necked flask for prepolymerization at 80°C for 1 hour, and then 10 μL of dibutyltin dilaurate was added to continue the reaction for 2 hours, followed by the addition of 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone to continue the reaction for 3 hours. After the reaction was completed, the system was cooled to 35°C and 8 mmol of triethylamine was added to react for 30 minutes, and finally 50 mL of deionized water was added and stirred for 20 minutes to obtain waterborne polyurethane.
[0086] Weigh 1.6 g of anhydrous ferric chloride and 5.9 g of sodium citrate dihydrate and dissolve them in 160 mL of deionized water. Then add 2 g of thiourea to the solution and then gradually add 2 g of sodium polyacrylate. Stir at room temperature at 500 rmp for 8 h. Then add the solution into a polytetrafluoroethylene-lined stainless steel reactor and react at 200 °C for 12 h to generate ferrosoferric oxide.
[0087] 400 mg of ferroferric oxide and 1000 mg of waterborne polyurethane were weighed and uniformly mixed to prepare a ferroferric oxide@waterborne polyurethane mixed solution. The ferroferric oxide@waterborne polyurethane mixed solution was poured into a polytetrafluoroethylene mold and allowed to stand in an open system for 7 h to obtain a single-layer ferroferric oxide@waterborne polyurethane composite absorbing material.
[0088] Performance Testing
[0089] The performance test of the absorbing materials prepared in Examples 1-3 and Comparative Examples 1-3 was carried out, wherein the electromagnetic parameters were tested by the coaxial transmission reflection method, the testing instrument was the Agilent-MS46322B vector network analyzer, and the test frequency range was 2-18 GHz. The samples were cut into ring-shaped samples with an inner diameter of 3 mm and an outer diameter of 7 mm by a cutter and then tested again. The absorbing properties of multi-layer waterborne polyurethane-based composite absorbing materials with different matching thicknesses, as well as single-layer waterborne polyurethane absorbing materials, single-layer MXene@waterborne polyurethane composite absorbing materials, and single-layer ferroferric oxide@waterborne polyurethane composite absorbing materials were obtained.
[0090] like Figure 1 This is a schematic diagram of microwave loss of the absorbing material prepared in Examples 1-3, wherein the absorbing material comprises a reflection layer, a matching layer, an absorption layer and a matching layer from bottom to top, wherein the reflection layer is MXene@aqueous polyurethane, the absorption layer is ferroferric oxide@aqueous polyurethane, and the matching layers are all aqueous polyurethane. In the absorbing material, electromagnetic waves undergo an "absorption-reflection-reabsorption" process, wherein the electromagnetic waves entering the absorption layer are first absorbed, and the remaining electromagnetic waves are reflected by the reflection layer and reabsorbed by the absorption layer. This absorption process effectively reduces the reflection of the incident electromagnetic waves, thereby reducing their secondary pollution to the environment.
[0091] Figure 2 The XRD pattern of the absorbing material prepared in Example 2 shows that ° The peak at corresponds to Ti3C2T x The (002) crystal plane of the MAX phase is located at 30.4 ° , 35.7 ° , 43.3 ° , 53.9 ° , 57.4 ° and 62.9 ° The peaks correspond to the (220), (311), (400), (422), (511) and (440) crystal planes of Fe3O4. ° The broad peak at corresponds to the diffraction peak corresponding to the amorphous waterborne polyurethane.
[0092] Figure 3 This is a SEM image of the absorbing material prepared in Example 2. It can be seen from the figure that the MXene@aqueous polyurethane reflective layer is placed on the bottom layer of the composite material, and the ferroferric oxide@aqueous polyurethane as the absorption layer is placed on the upper layer of the composite material. The upper and lower layers are respectively encapsulated with aqueous polyurethane, and there are no pores or gaps between the layers.
[0093] Figure 4-9The microwave loss capacity of the absorbing materials with different thicknesses prepared in Examples 1-3 and Comparative Examples 1-3 varies with frequency. It can be seen from the figure that compared with Comparative Examples 1-3, the absorbing performance of the multi-layer waterborne polyurethane-based composite absorbing materials prepared in Examples 1-3 is significantly optimized, indicating that the multi-layer structure design of the multi-layer waterborne polyurethane-based composite absorbing materials can significantly improve the absorbing performance; Figure 5 It can be seen that the microwave attenuation capability of the multilayer waterborne polyurethane-based composite absorbing material prepared in Example 2 reaches -50 dB when the thickness is 2 mm, and its microwave attenuation capability is significantly better than that of Comparative Examples 1-3. This indicates that the structure of the multilayer waterborne polyurethane-based composite absorbing material causes multiple reflections and scatterings of the incident electromagnetic waves between layers, effectively absorbs and attenuates the microwave energy, and improves the impedance matching of the material, thereby giving the multilayer waterborne polyurethane-based composite absorbing material excellent absorbing performance.
[0094] Fig.10 This is a stress-strain curve of the multi-layer waterborne polyurethane-based composite absorbing material prepared in Example 2. It can be seen from the figure that its tensile strength is 3.17 MPa and its elongation at break is 664%. This is because the waterborne polyurethane gives the multi-layer waterborne polyurethane-based composite absorbing material good flexibility, which increases the application scenarios of the composite material.
[0095] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A multi-layer waterborne polyurethane-based composite absorbing material, characterized in that: The multi-layer waterborne polyurethane-based composite absorbing material comprises a reflection layer, a matching layer, an absorption layer, and a matching layer from bottom to top; the reflection layer is MXene@waterborne polyurethane, the matching layers are all waterborne polyurethane, and the absorption layer is ferroferric oxide@waterborne polyurethane; The method for preparing the multi-layer waterborne polyurethane-based composite absorbing material is carried out in the following steps in sequence: (1) Preparation of waterborne polyurethane 22 mmol of isophorone diisocyanate and 10 mmol of polytetrahydrofuran were placed in a three-necked flask and prepolymerized at 80-100°C for 1-3 h, then 10 μL of dibutyltin dilaurate was added and reacted for 2-4 h, then 2 mmol of curcumin, 8 mmol of dihydroxymethylpropionic acid and 20 mL of acetone were added and reacted for 2-4 h, finally the system was cooled to 25-40°C and 8 mmol of triethylamine was added and reacted for 20-40 min, and then 50 mL of deionized water was added and reacted for 10-30 min to obtain waterborne polyurethane; (2) Preparation of MXene Put hydrochloric acid in a polytetrafluoroethylene beaker and slowly add lithium fluoride to react at room temperature and 500-800 rpm for 3-8 min, then slowly add titanium carbide and transfer the beaker to a 50-70°C oil bath, stir and react at 600-800 rpm for 8-14 h, then centrifuge the solution for the first time, wash with 0.5-2 mol / L hydrochloric acid and ultrapure water respectively until the solution is neutral, finally add 20 mL of ultrapure water to the centrifuge tube, shake for 20-40 min and centrifuge for the second time to obtain a MXene solution; (3) Preparation of Fe3O4 Dissolve 1.6 g of anhydrous ferric chloride and 5.9 g of sodium citrate dihydrate in 160 mL of deionized water in sequence, then add 2 g of thiourea to the solution, then gradually add 2 g of sodium polyacrylate, stir at room temperature at a speed of 300-500 rpm for 8-14 h, then add the solution to a polytetrafluoroethylene-lined stainless steel reactor, and react at 160-220°C for 8-14 h to generate ferrosoferric oxide; (4) Preparation of multi-layer waterborne polyurethane-based composite absorbing materials MXene and ferroferric oxide are mixed with waterborne polyurethane to obtain MXene@waterborne polyurethane and ferroferric oxide@waterborne polyurethane respectively; The mass ratio of the MXene to the waterborne polyurethane is 200:1000, and the mass ratio of ferrosoferric oxide to the waterborne polyurethane is 100-600:1000; 1200 mg MXene@waterborne polyurethane was added into a polytetrafluoroethylene mold and the system was opened and allowed to stand. Then, 400 mg waterborne polyurethane, 1100-1600 mg ferrosirroxide@waterborne polyurethane, and 400 mg waterborne polyurethane were added into the mold in sequence, and the system was opened and allowed to stand in sequence to obtain a multilayer waterborne polyurethane-based composite absorbing material.
2. A multi-layer waterborne polyurethane-based composite absorbing material according to claim 1, characterized in that: In step (2), the molar ratio of hydrochloric acid, lithium fluoride and titanium aluminum carbide is 22.5:4.75:
1.
3. A multi-layer waterborne polyurethane-based composite absorbing material according to claim 1, characterized in that: In step (2), the speed of the first centrifugation is 4000-7000 rpm, and the time is 5-20 min; the speed of the second centrifugation is 2000-5000 rpm, and the time is 10-30 min.
4. The multi-layer waterborne polyurethane-based composite absorbing material according to claim 1, characterized in that: In step (4), the standing time is 6-12 h.
Citation Information
Patent Citations
Three-layer composite wave-absorbing film and preparation method thereof
CN102179965A
Waterborne polyurethane-MXene electromagnetic shielding bionic nanocomposite material film and preparation method
CN110698847A
MXene / zinc-manganese ferrite / foamed silicone rubber wave-absorbing composite material as well as preparation method and application thereof
CN114058186A
Ti3C2Tx-based multilayer wave-type terahertz wave super-strong absorbing material
CN116423930A